Financial performance and stock prices into delisting companies in MSE (Desempeño financiero y precios de las acciones en companias delistadas en la BMV) - García, Heriberto (Facultad de Contaduría Pública y Administración U.A.N.L., 2013)
Abstract. After the adoption of new regulations in Corporate Governance practices and Transparency following the trend of international financial markets, Mexican Stock Exchange has decreased in number of public companies during the last three decades we explored a comprehensive list of delisted companies during the same period to analyze and understand the motives and reasons of the deregistration process in Mexico. Delisted companies in MSE has experienced low financial performance and unexpected stable stock prices, our results are related with systemic flaw in regulation, insider information and the opportunity to the MSE to increase in size and number of public companies.